Comparative politics of the third world - Green, December; Luehrmann, Laura (New Delhi, 2007)
This book offers just the right blend of theory and substanceto introduce students in a meaningful way to the developing -- or not developing--world. Avoiding overgeneralization on the one hand and the problems of astrictly country-by-country approach on the other, the authors consistently link concepts pertaining to history, politics, economics, andinternational relations to a set of eight case studies: the "classic"cases of Mexico, Nigeria, Iran and China, and the "alternative" casesof Peru, Zimbabwe, Turkey and Indonesia.
Keywords: International economic system